Identitas Finansial Anak Usia Dini melalui Pendekatan Sosiokultural dalam Literasi Keuangan - Titi Lestari; Muchammad Najiich (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Global economic developments demand increased financial literacy from an early age as a foundation for life skills and economic independence. Children build financial understanding not only through mathematical knowledge but also through social and cultural interactions within the family and school environment. This study aims to explore the formation of financial identity in early childhood through a sociocultural approach by reviewing literature on financial education practices in early childhood education (PAUD). The research method used a qualitative approach based on library research with a constructivist paradigm and Vygotsky's sociocultural theory. Data were collected through a literature review of journals, books, and policy documents related to early childhood financial education published between 2020 and 2025. The results show that children's financial identity is formed through a complex interaction between family cultural values, learning practices in PAUD, and exposure to digital media. Children gain an understanding of the concepts of money, saving, needs, and wants through direct experiences such as buying and selling simulations and market day activities. The findings also show differences in financial values ​​based on cultural background, with Chinese culture emphasizing saving and investment, while Sundanese culture emphasizes the value of sharing. This research confirms that integrating sociocultural-based financial education into the early childhood education curriculum can strengthen children's cognitive skills and social attitudes toward money.